Impact of educational intervention on knowledge regarding safe handling of cytotoxic drugs among the nursing personnel working in BPKIHS - Shrestha (Rai), Dev Kumari; Lama, S; Badu, A; Mandal, G N (Health Renaissance, 2017)
Introduction: Cytotoxic drugs are toxic compounds and are known to have carcinogenic, mutagenic and/or teratogenic potential. It is also considered as hazardous drugs. With direct contact they may cause irritation to the skin, eyes, and mucous membranes, and ulceration and necrosis of tissue. Safe handling refers to the process in which health care workers adhere to evidence-based practices (EBP) set forth by national organizations that have been designed to eliminate or significantly reduce occupational exposure. The key to safe handling is to protect the health care worker throughout the three phases of contact with the hazardous drugs. These phases are drug preparation, administration and disposal. Objective: To assess the effectiveness of education in enhancing the knowledge regarding safe handling of cytotoxic drugs among nursing personnel working at BPKIHS. Methods: Fifty nurses were taken as sample from selected ward of BPKIHS. One group pretest post test design was used by using population enumeration methods. Results: The overall mean score of knowledge on safe handling cytotoxic drugs of the respondents were 35.3 in the pre-test which increased to 83.7 in the post-test after an educational intervention. The difference was significant (p<0.001). Conclusion: Thus, the study's findings highlighted that there was a significant improvement in knowledge of the staffs after educational intervention. The educational intervention was very effective to improve the knowledge of the staffs. Health Renaissance 2015;13 (1):